HUBUNGAN DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP PASIEN DIABETES MELITUS DENGAN ULKUS DIABETIK - Quyumi Rahmawati, Elfi; Samsudin, Safrudin (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Family participation is one of the keys to success for diabetes patients in achieving the desired blood sugar targets. Diabetes patients who struggle to control blood sugar levels with family support will achieve their targets more quickly than if they struggled alone without a support system. Successful diabetes therapy is not only carried out by the patient and doctor, but must also be supported by support from the environment, in this case the family. The aim of this research is to determine the relationship between family support and quality of life in diabetes mellitus patients with diabetic ulcers in the Kaimana Regional Hospital. The design of this research is an observational analytic approach cross-sectional. The population in this study was 43 diabetes mellitus patients. The statistical test used is Chi-square with significance p value < 0,05. Based on test results chi square with a significant level of 5%, it was found that p = 0.063 < 0.05 showed that family support was lacking, while low quality of life was p = 0.088 < 0.05. There is a relationship between family support and quality of life in diabetes mellitus patients with diabetic ulcers at Kaimana Hospital, Kaimana Regency.